Domain of convergence of the Euler transform for the power series of an analytic function - Sukhorolskyi, M. A. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We consider the Euler transform of the power series of an analytic function playing the role of its expansion in a series in a system of polynomials and study the domain of convergence of the transform depending on the parameter of transformation and the character of singular points of the function. It is shown that the transform extends the function beyond the boundaries of the disk of convergence of its series on the interval of the boundary located between two singular points of the function. In particular, it is established that the power series of the function whose singular points are located on a single ray is summed by the transformation in the half plane.